2015
DOI: 10.1038/srep10058
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic near-field optical interaction between oscillating nanomechanical structures

Abstract: Near-field optical techniques exploit light-matter interactions at small length scales for mechanical sensing and actuation of nanomechanical structures. Here, we study the optical interaction between two mechanical oscillators—a plasmonic nanofocusing probe-tip supported by a low frequency cantilever, and a high frequency nanomechanical resonator—and leverage their interaction for local detection of mechanical vibrations. The plasmonic nanofocusing probe provides a confined optical source to enhance the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…For instance, if one actuates a mechanical structure in the in-plane direction, interferometric techniques tend to become insensitive to the mechanical motion. Recently demonstrated transduction techniques suitable for such motions are primarily based on optical scattering: optical knife-edge technique [ 105 , 106 , 107 ], and scattering enhanced with near-field optical probes and/or approaches [ 59 , 63 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Detection Of Nanomechanical Motionmentioning
confidence: 99%
“…For instance, if one actuates a mechanical structure in the in-plane direction, interferometric techniques tend to become insensitive to the mechanical motion. Recently demonstrated transduction techniques suitable for such motions are primarily based on optical scattering: optical knife-edge technique [ 105 , 106 , 107 ], and scattering enhanced with near-field optical probes and/or approaches [ 59 , 63 , 108 , 109 , 110 , 111 , 112 , 113 , 114 ].…”
Section: Detection Of Nanomechanical Motionmentioning
confidence: 99%
“…Unfortunately, the widespread use of antibiotics has increased bacterial resistance, leading to delayed administration of effective therapy as well as morbidity and mortality in both humans and animals 8 9 . As reported, antimicrobial-resistant infections cause more than 700,000 deaths each year globally: at least 23,000 in the USA and 175,000 in the EU 10 11 . Furthermore, the development of new antibiotics has slowed down, and few antibiotics have been approved by the FDA in recent years 10 .…”
mentioning
confidence: 99%
“…As reported, antimicrobial-resistant infections cause more than 700,000 deaths each year globally: at least 23,000 in the USA and 175,000 in the EU 10 11 . Furthermore, the development of new antibiotics has slowed down, and few antibiotics have been approved by the FDA in recent years 10 . Moreover, recent studies have reported that therapeutic or sub-therapeutic antibiotic treatments in early life have long-term consequences on intestinal microbiota composition and metabolic homeostasis in the host 12 13 .…”
mentioning
confidence: 99%
“…Very recently, a beating response due to interference of two oscillatory modes with close frequencies has been found in a nanomechanical resonator. 23 It is important to make experimental measurements of the response of CNTs at high temperature. This should be possible having significant influence for a CNT as an AFM cantilever and a mass sensor.…”
Section: Discussionmentioning
confidence: 99%
“…[15][16][17][18] It is well known that nonlinearity may play an important role in the thermal and electrical transport of nanotubes, nanoribbons and nanowires. [19][20][21][22][23] For nonlinear vibration of CNTs actuated by a direct current (DC) or alternating current (AC) load, it has been found that the type vibration may suddenly transition from a planar motion to a whirling, "jump rope" like motion. 24,25 The effect of initial curvature of CNTs has also been investigated using a two dimensional nonlinear curved beam model, and it shows the transfer of energy among the vibration modes involved in the veering phenomenon.…”
Section: Introductionmentioning
confidence: 99%